(Re)construir utopias: jovem, cidade e política - Cassab, Clarice (2009)
The aim of this work is understand how the territory became an important element in the contemporary youth behavior. Specifically, how the city, through their appropriation, may be understood as a central aspect in the building of new ways of youth action and also in the conception of their politics. Two programme with youth occurring in the Juiz de Fora, a medium economic city of Zona da Mata mineira , support this work: UFJF (Territory of Opportunity) and Juiz de Fora on Track of Peace. The thought is build by the analyze of differents meaning for young people and youth, their way of actions and intervention and also in the relationship establish between the young people and the city. The challenge is to think in which way the city can be an important aspect in the building of new social actions, trying to recover the use of territory as a way of space appropriation and also the social-territory practice which keep a dimension practical- sensitive of the life in the city allowing the action direction.